Electrochemical Determination of Propiconazole Residues in Grain samples by Voltammetry at Carbon Nanotubes Paste Electrodes (Global Journal of Science Frontier Research, 2018)
In this study the residues of propiconazole in grains samples determined on the basis of its reduction behavior at carbon nanotubes paste electrodes. The reduction product is identified by using cyclic voltammetry and the universal buffer with pH range 2.0-6.0 is used as supporting electrolyte. The best curve and highest peak current are obtained in universal buffer at pH 4.0. Accumulation potential, Accumulation time and Scan rate were optimized. Calculations made of by standard addition method. The peak heights are in linear trend over the concentration range of 1.02 x 10 -9 to 1.05 x 10 -10 M. The relative standard deviation and correlation coefficient for propinacazole is 0.97% and 0.998 respectively.
Keywords: propiconazole; carbon nano tubes paste electrodes; DP-ASV; cyclic voltammetry; universal buffer; grains samples